Congenital duplicated ureter-vagina anomalous anastomosis causing female urinary incontinence: a case report and literature review - Li, Shuxin; Cao, Hongliang; Zhang, Yueqiu; Su, Jinghan; Yang, Tong; Wei, Wei; Lian, Xin (Frontiers in Pediatrics, 2025)
Ectopic ureter is a rare congenital anomaly, often challenging to diagnose due to atypical anatomical positioning and variable clinical presentations. Consideration should be given to the possibility of an ectopic ureteral orifice in young women presenting with persistent, unexplained urinary incontinence. This report details a 22-year-old nulliparous female presenting with persistent urinary incontinence. Imaging revealed left ureteral dilatation, with CT suggesting a possible connection between the distal ureter and vagina. Magnetic resonance imaging of the urinary system confirmed bilateral renal abnormalities with double ureteral malformations, hydronephrosis on the left side, and ectopic opening of the left ureter into the anterior vaginal wall, accompanied by a bicornuate uterus. Cystoscopy confirmed a double ureteric orifice on the right side and an ectopic left ureteral opening into the vagina. The patient underwent intraoperative cystoscopy, ureter cystostomy, and double-J stent placement. At the two-month post-operative follow-up, the patient's urinary incontinence symptoms and left-sided hydronephrosis with ureteral dilatation had completely resolved. Normal urinary function was restored, and the double-J stents were successfully removed via cystoscopy. This case underscores the need for heightened vigilance regarding congenital ectopic ureteral orifices in young women with no history of childbirth or surgery presenting with urinary incontinence. The combination of cystoscopy and imaging aids in definitive diagnosis, with surgical reimplantation yielding favorable outcomes. Early identification and intervention are crucial for improving prognosis.